Soe English Teachers’ Belief and Actions in Indonesian Merdeka Curriculum - Heidy Wulandari (Indonesian Postgraduate Foreign Language Education Association, 2024)
This study aimed at exploring Soe English teachers believes and actions in Indonesian Merdeka curriculum. The method used was descriptive qualitative research with in-depth interview on 3 Soe English-teachers as the participants. The data were analyzed qualitatively through transcription, coding, and categorization. The result shows that Soe teachers’ action is in line with their belief on Merdeka Curriculum which is formed by their background and the way they believe in curriculum change. As their background, two teachers teach in rural area, the first one has limited school facilities and students with limited ability, while the second one has supportive facilities but the male students are low learners. The former strongly believed in curriculum change due to the adaptation to time change. The latter believed that Merdeka curriculum is great but consideration needs to be taken on schools’ ability to adapt to curriculum change. The third teacher teaches in capital city with supporting school facilities and students with various backgrounds which demands him to treat the students differently according to their need. This teacher firstly disagreed but then mentioned about teacher’s duty to adapt to curriculum change. Their background and the way they view curriculum change from their belief which influenced their action in implementing Merdeka curriculum. They come to having efforts in improving knowledge on Merdeka curriculum, designing modules, having creative ways of implementing Merdeka curriculum, recognizing what is needed by schools and students to implement Merdeka curriculum, designing assessment, and facing obstacles in Merdeka curriculum implementation.